Food exchange list based on macronutrients: adapted for the Ecuadorian population - Chisaguano-Tonato, Aida Maribel; Herrera-Fontana, María Elisa; Vayas-Rodriguez, Gabriela (Frontiers in Nutrition, 2023)
Background: Food exchange lists allow health professionals to generate healthy eating plans adapted to individual or population needs. The objective of this study was to develop the first food exchange list based on the macronutrients and energy provided by the various food groups of the Ecuadorian diet.The list of Ecuadorian food exchanges was constructed by going through the following phases: 1) Selection of household measurements; 2) Selection of tables and databases of the nutritional composition of food items; 3) Definition of food groups and quantities; 4) Determination of the average energy and macronutrient values of each group; and 5) Photographic record. For the definition of food quantities, statistical criteria were applied according to a standard deviation of ±2SD; thus, for carbohydrates: ±5g, total fat: ±2g, and protein: ±3g. To ensure the inclusion of the food items in the groups, a coefficient of variation of less than 30% and a Z value of ±2 were also considered.The list of food exchanges is presented with eight general groups according to the predominant nutrient (carbohydrates, proteins, or fats), and, where necessary, subgroups are included according to the second predominant nutrient. The list includes 404 food items with their photographic record, represented by their net weights and corresponding household measurement. All food items met the statistical criteria that help to reduce the variability of the nutritional composition of the food items in each group.This is the first list of Ecuadorian food exchanges based on the application of statistical criteria and that includes photographic support for all the exchange portions. It will allow 2 This is a provisional file, not the final typeset article nutritionists, dieticians, and researchers to generate healthy eating plans and guidelines according to Ecuador's cultural and dietary patterns.